Crystal and Magnetic Structure of Sr2MIrO6 (M = Ca, Mg) Double Perovskites – A Neutron Diffraction Study. Issue 1 (2nd December 2013) - Kayser, Paula; Martínez‐Lope, María Jesús; Alonso, Jose Antonio; Retuerto, María; Croft, Mark; Ignatov, Alexander; Fernández‐Díaz, Maria Teresa
Abstract: Sr2 CaIrO6 and Sr2 MgIrO6 double perovskites have been prepared as polycrystalline powders from citrate precursors treated under oxygen pressure conditions. These compounds have been studied by X‐ray and neutron powder diffraction (NPD), magnetic measurements, and X‐ray absorption spectroscopy. The crystal symmetry of both oxides is monoclinic (space group P2 1 / n ), and the unit‐cell parameters are related to the ideal simple perovskite cell as a ≈ √2 a 0, b ≈ √2 a 0, c ≈ 2 a 0, β ≈ 90°, where a 0 is the edge of the simple cubic ABO3 perovskite. This superstructure is a result of the 1:1 ordering of Ca/Mg and Ir ions over the B site and the distortion of the oxygen sublattice, which leads to a tilted three‐dimensional network of corner‐sharing BO6 octahedra. Magnetic measurements indicate an antiferromagnetic ordering below T N = 58 K for Sr2 CaIrO6 and 74 K for Sr2 MgIrO6 . The low‐temperature magnetic structure of Sr2 CaIrO6 was determined by NPD and selected from the possible magnetic solutions compatible with the P 21 / n space group according to the group‐theory representation. The propagation vector is k = (1/2 1/2 0). A canted antiferromagnetic structure is observed below T N with an ordered magnetic moment of 1.33(2) μ B for the Ir 6+ cations. Sr2 MgIrO6 does not present magnetic reflections. An X‐ray absorption spectroscopy investigation gives an insight into the Ir oxidation states and suggests a hexavalent state for the Ca compound and an admixture of Ir 6+ and Ir 5+ for the Mg perovskite, in agreement with the NPD data, which indicate a significant oxygen understoichiometry for this material. Abstract : The title perovskites were stabilized under oxygen pressure conditions. They show 1:1 ordering of Ca/Mg and Ir ions over the B site of monoclinic P2 1 / n superstructures consisting of a tilted three‐dimensional network of corner‐sharing BO6 octahedra. The magnetic structure of Sr2 CaIrO6 below T N = 58 K, with propagation vector k = (1/2 1/2 0), is a canted antiferromagnetic arrangement of Ir 6+ moments.